Nongovernmental International Human Rights Organizations: The Case of Hong Kong. Issue 3 (19th June 2014) - Lam, Wai-man
ABSTRACT This article examines the contributions of nongovernmental international human rights organizations (NGIHRO) in promoting a broad sense of human rights in hybrid regimes using the cases of Amnesty International Hong Kong (AIHK), Green Peace Hong Kong (GPHK), and Oxfam Hong Kong (OHK). It contends that NGIHROs have made significant contributions to public education and fund-raising in Hong Kong. However, with regard to the human rights conditions, it is erroneous to consider Hong Kong as part of the developed world. Together with other probable political considerations, doing so may have led to gaps in the organizations' roles and functions as advocates for human rights in Hong Kong. In the final analysis, this article uses the political protests in Hong Kong to illustrate the importance of addressing the implications of demands for preserving the local identity and alternative lifestyles in the broader understanding of human rights.